2016
DOI: 10.1590/1678-457x.0032
|View full text |Cite
|
Sign up to set email alerts
|

Sensory response and physical characteristics of gluten-free and gum-free bread with chia flour

Abstract: The aim of this study was to evaluate the physical quality and sensory acceptance of gluten-free breads with different percentages of chia flour (Salvia Hispanica L.). The chia flour was used to substitute rice flour and soy flour in order to replace the gum required in this type of bread. Four formulations were developed; a standard made with gum, and three formulations with 2.5%, 5.0% and 7.5% of chia flour. Analyses of specific volume, cooking losses and the rise in dough of the breads were performed. Senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Similarly, other authors investigating chia seed supplementation did not report deterioration of the sensory qualities of the analyzed bread types. Huerta et al () demonstrated that replacement of soybean and rice flour with 2.5% of chia seeds yielded gluten‐free bread with sensory traits similar to those of the control bread. In turn, Iglesias‐Puig and Haros () reported that the addition of chia seeds to cereal products enhanced overall consumer acceptability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, other authors investigating chia seed supplementation did not report deterioration of the sensory qualities of the analyzed bread types. Huerta et al () demonstrated that replacement of soybean and rice flour with 2.5% of chia seeds yielded gluten‐free bread with sensory traits similar to those of the control bread. In turn, Iglesias‐Puig and Haros () reported that the addition of chia seeds to cereal products enhanced overall consumer acceptability.…”
Section: Resultsmentioning
confidence: 99%
“…Chia seeds have been used in bakery products (Bustos et al, 2017;Costantini et al, 2014;Farrera-Rebollo et al, 2012;Huerta, Alves, Silva, da Kubota, & Rosa, 2016), but there is no information available about the use of a by-product of chia oil extraction. The aim of this study was to investigate the effects of the addition of chia waste on the quality of wheat and gluten-free breads and to compare the effects of adding the waste with the effects of adding whole seeds.…”
mentioning
confidence: 99%
“…On the other hand, Burgos and Armada () demonstrated amaranth suitability to precooked products due its high expansion and yellow index. Chia flour was incorporated at different levels in cakes (25%, 50%, and 75%) (Borneo and others ), corn tortillas (5%, 10%, 15%, and 20%) (Rendón‐Villalobos and others ), and gluten‐free bread (from 4% to 15%) (Moreira and others ; Steffolani and others ; Da Mota Huerta and others ). Chia flour played the role of hydrocolloid, indeed, because it significantly increased the water‐holding capacity of the dough (Olivos‐Lugo and others ; Steffolani and others ; Da Mota Huerta and others ).…”
Section: Ancient Grains‐based Foodstuffs: Nutritional Added Value Andmentioning
confidence: 99%
“…observed no significant differences in replacing rice and soy flour with 2.5%, 5.0%, and 7.5% whole chia flour in specific volume, baking loss, and sensory acceptability (scores ranging from 4.5 to 5.5, on a 7-point hedonic scale) on GF bread in comparison to control. [ 40 ] In another study, 2.5%–7.5% whole chia flour was used in chestnut flour-based GF bread formulation. They found improved in the dough rheological properties of elasticity, viscosity, and stability up to using 7.5% chia flour.…”
Section: Different Source Of Gluten-free Flourmentioning
confidence: 99%